Strategi Pemasaran Penerimaan Mahasiswa Baru Pasca Perubahan Bentuk Dari Akademi Manajemen Belitung Ke Politeknik Belitung - Alfin Yuan Octavedha (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
New student admissions play an important role in the continuity and teaching process in universities, especially at Politeknik Belitung. Improving the quality of university in terms of the quality of education and services greatly affects the confidence level of new students to choose Politeknik Belitung as the university where they study. One way to improve the quality of higher education is to upgrade deformed from Academy to a Politeknik, along with increase number of study programs. Planning a good marketing strategy concept and implementing the right marketing strategy will play an important role in achieving the target number of new student admissions. This article shows several strategies that can be used by the Politeknik Belitung through the new student admissions committee including by conducting socialization, using social media and utilizing existing resources by utilizing institutions, communities and people who are connected to the Politeknik Belitung, especially alumni who have completed education at Politeknik Belitung